The Moral Damage in the Provisions of the Administrative Justice - Jenan A. Fattah (Journal of Madenat Alelem University College, 2016)
The compensation in any form it would be compatible with the modern law state with democratic orientation in which the administration will subject to the authority of the judiciary in obligating the granting compensation for the damages affected the individuals. These damages can be easily compensated but not all damages will be in the form of material loss by the administration towards the individuals. Some kinds of damages might raise some problems while prompting or compensating such as moral damages. These damages affect the individual in the moral side and caused him pain, sadness, suffer and concern. Thus, the administration could not compensate with an amount of money to remove such damage. The French Council of State was the first to take of the compensation for moral damages. Though this council has refused compensation for moral damages and headed towards compensation for material damage only, eventually it began a new era of embraced the policy of compensation for moral damages and met with the other ordinary justice. This new approach fined entire welcome by the common law jurisprudence in France. With this approach a new era of fairness was born. The administrative court was in need for it to increase the public confidence in its justice.